Trade-employment linkage of FTAs in Korea: Inter- and intra-industry reallocations of production resources. (6th November 2018) - Jang, Yong Joon; Cho, Mee Jin; Kim, HanSung
Abstract : Purpose: The purpose of this paper is to empirically examine the link between trade liberalization and employment through the export channel under Korea's FTAs by distinguish firm heterogeneity (i.e. size) as well as sector-level international competitiveness (i.e. comparative advantage). Design/methodology/approach: Using the firm-level data during 2000–2009, the authors drive the difference-in-difference-in-difference model on Wagner (2007) with the dependent variables of labor productivity and employments and the independent variables of free trade agreement, revealed comparative advantage, firm size and payroll costs. Findings: The authors find that the economic benefit of FTAs in Korea is not concentrated in large enterprises or firms with comparative advantage. Accordingly, the authors conclude that FTA or trade liberalization brings positive effects to business as a whole, rather than to specific industries or group of firms. Research limitations/implications: The Korean Government has continued its policy of supporting small and medium-sized enterprises (SMEs) for a long time by recognizing them as socially underprivileged. According to the results of this study, an increase in export through FTAs improves firm's labor productivity and increases employment, especially for SMEs, which can be a practical and efficient support for them. Originality/value: The paper provides the empirical evidences that how the effects of trade liberalization on labor depend on firm heterogeneity, industrial competitiveness and/or both and thus how labor is reallocated in response to trade liberalization in Korea.